Multi-element co-doped biomass porous carbon with uniform cellular pores as a supercapacitor electrode material to realise high value-added utilisation of agricultural waste. Issue 32 (25th July 2022) - Yue, Xiandong; Yang, Haixia; An, Ping; Gao, Zexing; Li, Haokun; Ye, Feng
Abstract : Biomass-based porous carbon materials have attracted considerable attention because of their simple, low-cost, green, and pollution-free preparation process. Abstract : Biomass-based porous carbon materials have attracted considerable attention because of their simple, low-cost, green, and pollution-free preparation process. Owing to their unique tubular structure and subsequent activation process, they often have a well-developed pore structure. Biomass-based carbon materials with three-dimensional hierarchical pores and polyatomic doping are regarded as promising electrode materials in the field of energy storage. In this study, cornstalk was used as the biomass and a pioneering approach was used to prepare porous carbon co-doped with N, B, and P. The B, N, P-codoped porous carbon has a three-dimensional honeycomb-like network structure with uniformly distributed and interwoven macro-, meso-, and micropores. Furthermore, it has an ultra-high specific surface area of 3123.5 m 2 g −1, a high specific capacitance of 342.5 F g −1 at a current density of 0.5 A g −1, and an energy density of up to 26.18 W h kg −1 . This study demonstrates a multi-element co-doping strategy that enhances the performance of cornstalk as a precursor of a supercapacitor electrode material and has important implications in the high-value-added utilisation of waste straw.